2000
DOI: 10.1034/j.1600-0706.2000.890118.x
|View full text |Cite
|
Sign up to set email alerts
|

Predator‐induced life‐history changes and the coexistence of five taxa in a Daphnia species complex

Abstract: Interspecific hybridization is common in water fleas of the Daphnia galeata species complex (e.g. D. galeata, D. cucullata, D. hyalina and their interspecific hybrids). We studied the effect of fish on the life histories of five taxa of this species complex originating from the Plußsee, northern Germany. Using four clones per taxon, we found that fish kairomones reduce size at birth and size at maturity significantly. For size at maturity larger taxa showed a significantly stronger reaction to fish kairomones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 60 publications
6
54
0
Order By: Relevance
“…Thus, our results do not support two important claims made previously in literature. First, the effect of fish kairomones was not stronger in larger zooplankton species known for their greater susceptibly to size-selective visual predation (Boersma et al 1996, Spaak et al 2000. Second, it was not weaker due to the insufficient reduction of the risk of predation by life history adjustments (Sakwinska and Dawidowicz 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, our results do not support two important claims made previously in literature. First, the effect of fish kairomones was not stronger in larger zooplankton species known for their greater susceptibly to size-selective visual predation (Boersma et al 1996, Spaak et al 2000. Second, it was not weaker due to the insufficient reduction of the risk of predation by life history adjustments (Sakwinska and Dawidowicz 2005).…”
Section: Discussionmentioning
confidence: 91%
“…In this system, we studied the composition of the Daphnia population consisting of 20 clones from five parental and hybrid taxa. These clones had been previously investigated in life-history experiments (Spaak et al 2000), which demonstrated that there is a significant positive correlation between size at maturity (SAM) and intrinsic rate of increase, r. Based on these data, we expect the larger taxa D. galeata and D. galeata × hyalina to have the highest r, and hence dominate the Daphnia population numerically under conditions without fish kairomones. The differences with the other taxa are expected to become smaller when kairomones are added to the water, because of different migration strategies and changes in life histories.…”
Section: Introductionmentioning
confidence: 95%
“…For the hybrid D. galeata × hyalina very limited variation was found, therefore three out of the four clones we used had the same multi-locus genotype (MLG). This resulted in a set of 20 clones, with 15 different multi-locus genotypes (Table 1 in Spaak et al 2000).…”
Section: Field Site and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence generally presented supports the view that a phototactic reaction to relative changes in light intensity is at the basis of DVM. This phototaxis is enhanced by fish kairomones (Gliwicz 1986, Dodson 1990, Dodson et al 1997, Leibold 1990, Ringelberg 1991a, b, Bollens et al 1992, Lampert & Loose 1992, Haney 1993, Lampert 1993, Loose 1993a, b, Loose et al 1993, Ringelberg & Flik 1994, Spaak et al 2000, Von Elert & Pohnert 2000 and influenced by temperature (Gerritsen 1982), food and individual size (Angeli et al 1995, Worthington 1931. Ringelberg (1980) even classified the factors regulating DVM into two categories.…”
Section: Introductionmentioning
confidence: 99%